Clinical‐epidemiological and radiological characteristics of stroke patients: A multicentre study. Issue 12 (24th October 2021) - Kunt, Refik; Çınar, Bilge Piri; Yüksel, Burcu; Güllüoğlu, Halil; Sayılır, İdris and Çeliker Uslu, Sibel and Özaydın Göksu, Eylem and Bülbül, Nazlı Gamze and Yıldız, Baykal and Öz, Didem and Keskin, Ahmet Onur and Korucu, Osman and Akpınar, Çetin Kürşad and Solmaz, Volkan and Akpınar, Meliha and Altunç, Fatma Zehra and Elmas, Zeynep and Büyükuysal, Çağatay and Ekici, Mustafa and Güvendi, Güven
Abstract: Introduction and Aim: Stroke is the leading cause of disability in adults and the second most common cause of death, at a rate of 11.8% worldwide. The purpose of this study was to examine the aetiological, demographic, and clinical characteristics of patients admitted to hospital because of acute strokes. Materials and Methods: This multicentre study retrieved information for all patients admitted to hospital because of an acute cerebrovascular event over a six‐month period, and sociodemographic, aetiological, and clinical characteristics were recorded. Results: A total of 1136 patients, 520 of whom were women (45.7%), with a mean age of 70.3 ± 12.8 years, were included in the study. Of these, 967 were diagnosed with ischaemic stroke (IS) (85.1%), 99 with haemorrhagic stroke (HS) (8.7%), and 70 with transient ischaemic attack (6.1%). The most common risk factor for stroke was hypertension (73%). Carotid disease and hyperlipidaemia rates were higher in patients with HS. Numbers of functionally dependent patients with severe neurological status according to the National Institutes of Health Stroke Scale and modified Rankin scale were significantly higher in the HS group ( P < .001). When IS was classified according to the Trial of Org 10172 in Acute Stroke Treatment, small vessel disease emerged as the most common cause (41%). The most common lesion localisations were the parietal lobe (23%) in the IS group and the thalamus (35.3%) in the HS group. Eighty‐eight patients (7.7%), 62 (6.4%) in the ischaemic subgroup, and 26 (26.3%) in the haemorrhagic subgroup, died within the first month. Conclusion: Current and accurate evaluations of stroke aetiology are essential for stroke prevention and treatment planning. This study, shows that no change occurred in the aetiology of stroke and epidemiological characteristics and that accurate identification of modifiable stroke risk factors is still a major goal.